2020
DOI: 10.1177/2373379920963660
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Student Learning, Satisfaction, and Experiences Between Hybrid and In-Person Course Modalities: A Comprehensive, Mixed-Methods Evaluation of Five Public Health Courses

Abstract: Schools and programs of public health are expanding online course offerings, particularly in response to the transition to remote learning due to COVID-19. While previous research in the health professions suggests that online and in-person modalities are equally effective in supporting student learning, there is minimal evidence of this in public health education. This evaluation examines the effectiveness of newly developed online or hybrid course sections offered to Master of Public Health (MPH) and Master … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
1
19
0
2
Order By: Relevance
“…This study investigated if there was a differential impact based on instructional delivery mode (in-person vs. synchronous online) for a semester-long academic course about gender, sexuality, and sexual violence for first year first-semester students. Similar to other studies (Means et al, 2013(Means et al, , 2014Walker et al, 2021), we found minimal differences in student outcomes between the course modes. These findings add to the pedagogical literature by demonstrating that synchronous online instruction, due to COVID-19 or otherwise, can be an effective modality for teaching and learning about sexual violence, a critical health promotion issue.…”
Section: Implications For the Field Of Pedagogy In Health Promotion/p...supporting
confidence: 90%
See 1 more Smart Citation
“…This study investigated if there was a differential impact based on instructional delivery mode (in-person vs. synchronous online) for a semester-long academic course about gender, sexuality, and sexual violence for first year first-semester students. Similar to other studies (Means et al, 2013(Means et al, , 2014Walker et al, 2021), we found minimal differences in student outcomes between the course modes. These findings add to the pedagogical literature by demonstrating that synchronous online instruction, due to COVID-19 or otherwise, can be an effective modality for teaching and learning about sexual violence, a critical health promotion issue.…”
Section: Implications For the Field Of Pedagogy In Health Promotion/p...supporting
confidence: 90%
“…Students sometimes report deriving greater satisfaction from in-person courses than online courses due to increased faculty interaction and motivation (Young & Duncan, 2014). However, the two instructional modalities have been found to yield comparable learning outcomes based on researcher-created assessments, instructor-created assessments, and grade point averages (Aguilera-Hermida, 2020;Means et al, 2013Means et al, , 2014Walker et al, 2021).…”
Section: Covid-19 and The Shift To Online Instructionmentioning
confidence: 99%
“…Scull et al (2020) have cautioned conflating social media proficiency with general technology proficiency or assuming that students possess the ability to make use of digital platforms for educational purposes. Teaching staff delivering online or blended courses for the first time should receive training on the pedagogical differences between online and face-to-face delivery, take time to understand learner technology proficiency, and be offered the opportunity to co-teach with an experienced teaching staff member; and students should be adequately prepared for differences in online and face-to-face learning (Walker et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, survey findings highlight a preference for interactive activities rather than lecture content among students who prefer to study face-to-face. Choice remains important for students, with the option to enroll in a face-to-face mode where feasible and to select study modes that suit learning styles and schedules (Walker et al, 2020). Investigating the possible amplifying effects of receiving both on and offline experiences on learning and social support is recommended.…”
Section: Course Modalitiesmentioning
confidence: 99%
“…Attitudes regarding motivation toward learning are linked to achievement(Orsini et al, 2018) and satisfaction(Edgar et al, 2019) in health professions. Favorability and satisfaction as a perceived health professions student outcome warrants investigation, not only for its positive links to student attitudes and outcomes(Walker et al, 2021) but also for its accessibility and practical implications for faculty and course designers(Cleland et al., 2020), particularly those considering CoI. CoI presence is a clear positive predictor of student attitudes in online contexts.…”
mentioning
confidence: 99%